Potential and Optimization of Antibiotic Production Isolate Bacteria Antibiosis Bacillus sp. Origin of Salt Liquid Waste of Anchovy (Stolephorus Sp.) Against Bacteria Test - Nurmiati, Nurmiati; Dwisa Putra, Wahyu; Periadnadi, Periadnadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Waste is one of the environmental problems that exists in every fish processing industry. Therefore, other ways are needed so that fish processing waste can be reused into something more useful. The use of waste that can be used is by using antagonistic microorganisms as antibiotic producing materials. The aim of this research is to determine the partial characteristics and potential of antibiosis bacteria and to obtain isolates that have antibiosis potential against S. aureus and E. coli. Determine the effect of the best substrate protein, the effect of the best incubation time, the effect of the best pH conditions, the effect of the best salinity levels, the effect of the best trace elements for Bacillus sp species isolates. in the production of antibiotics against the test bacteria S. aureus and E. coli. And determine the best optimization of salted anchovy water production media in the production of antibiotics against the test bacteria S. aureus and E. Coli. The research method was carried out by survey and the results were presented descriptively. The results of this research obtained isolates of Bacillus sp. circular in shape, overall edges, raised elevation, and white in color. Basil cell form, motile bacteria, and has a Potential Antibiosis Index value of 1.95; Proteolytic Index 1.67; Fermentative 1.36; Amylolytic 1.18; Cellulolytic 1.79; and Lipolitics 1.26. Optimum conditions for the antibiosis bacterial isolate Bacillus sp. in producing antibiotics, namely on skim milk protein substrate, incubation time 16 hours, pH 6.73; trace element Zn, Salinity Content 5‰. The optimum condition for isolates in salted anchovy water media to produce antibiotics is at a salt content of 100% (11 ppt).